2023
DOI: 10.1039/d3sc01491f
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping aromatic frameworks: expansion of aromatic system drives metallabenzenoids to metallapentalenes

Abstract: Reshaping an aromatic framework to generate other skeletons is a challenging issue due to the stabilization energy of aromaticity. Such reconfigurations of aromatics commonly generate non-aromatic products and scarcely reshape...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Aromaticity study of metallacycloprop-1-ene complexes has been reported recently, and they show mainly σ-aromaticity. Such work on metallacycloprop-2-ene complexes is less developed though η 2 -alkyne complexes have been widely studied. , Since many fused metallacycloprop-1-enes are aromatic, herein we present the synthesis and characterization of fused five- and six-membered oxa-rhenacycles with a metallacycloprop-2-ene unit, as well as their aromaticity investigation.…”
Section: Introductionmentioning
confidence: 90%
“…Aromaticity study of metallacycloprop-1-ene complexes has been reported recently, and they show mainly σ-aromaticity. Such work on metallacycloprop-2-ene complexes is less developed though η 2 -alkyne complexes have been widely studied. , Since many fused metallacycloprop-1-enes are aromatic, herein we present the synthesis and characterization of fused five- and six-membered oxa-rhenacycles with a metallacycloprop-2-ene unit, as well as their aromaticity investigation.…”
Section: Introductionmentioning
confidence: 90%